Organic Matter Redox State Driven by Specific Sources in Mangrove Sediments: A Case Study from Peruvian Ecosystems - Alexander Pérez; Gerardo Cebrián-Torrejón; Noemí Montoya; Joan Piquero-Cilla; Christian J. Sanders; Antonio Doménech-Carbó; Wilson Machado (Journal of Marine Science and Engineering, 2021)
In order to determine the organic matter redox state in relation to specific sources in mangrove sediments, two 60 cm-long sediment cores were collected from mangrove-covered and mudflat zones within a mangrove forest in Peru. Sediment subsamples from these cores were analyzed to determine δ13C values and C:N ratios, whereas two redox indices, namely, electrochemical (fEAOM) and spectroscopical (A1650/A3400) indices, were taken from a previous study and correlated with the geochemical indices obtained from this work. These indices may provide accurate information on sedimentary organic matter diagenesis by oxidative processes through its redox state. The results show that the electrochemical index (fEAOM) and the spectroscopical index (A1650/A3400) for mangrove-covered sediments exhibited a positive correlation with δ13C values and a negative correlation with C:N molar ratios. These correlations suggest that the more labile sedimentary organic matter derived from non-terrestrial sources is in a more oxidized state than that derived from mangrove vegetation. However, this was not valid for mudflat zones, where non-significant correlations between geochemical indices were observed. Furthermore, the results suggest that the redox state of the organic matter deposited over time is dependent on source mixing influences, being better preserved in the presence of mangrove-derived organic matter.